Pathologic complete response to neoadjuvant anti-HER2 therapy is associated with HER2 immunohistochemistry score in HER2-positive early breast cancer. Issue 44 (5th November 2021) - Chen, Hai-long; Chen, Qiang; Deng, Yong-chuan
Abstract : Abstract: To evaluate whether pathologic complete response (pCR) to neoadjuvant anti-human epidermal growth factor receptor 2 (HER2) therapy is dependent on the HER2 immunohistochemistry (IHC) score. A total of 181 HER2-positive early breast cancer patients who had received neoadjuvant anti-HER2 therapy were included in this study. Associations were examined between IHC score and tumor pCR status (commonly defined by ypT0+ypN0, ypT0/is+ypN0, or ypT0/is). In trastuzumab-based neoadjuvant-treated patients, ypT0+ypN0 was achieved in 46.0% of patients with HER2 IHC 3+ tumors but only 25.0% of patients with HER2 IHC 2+/fluorescence in situ hybridization (FISH)-positive tumors ( P = .016). When pCR was defined as ypT0/is+ypN0 or ypT0/is, 54.7% and 61.3% of patients with HER2 IHC 3+ tumors had a pCR, whereas only 29.5% and 38.6% with HER2 IHC 2+/FISH-positive tumors achieved pCR ( P = .004 and P = .008, respectively). The association between dual HER2 blockade and pCR was almost exclusively confined to HER2 IHC 3+ tumors (ypT0+ypN0: 61.9% vs 38.9%, P = .013; ypT0/is+ypN0: 71.4% vs 47.4%, P = .009; and ypT0/is: 81.0% vs 52.6%, P = .002) and was absent in HER2 IHC 2+/FISH-positive tumors. Multivariate logistic regression revealed that HER2 IHC 3+ tumors had a significantly higher probability of achieving ypT0+ypN0 (odds ratio [OR], 0.265; 95% confidence interval [CI], 0.109–0.645; P = .003), ypT0/is+ypN0 (OR, 0.221; 95% CI, 0.094–0.521; P = .001), and ypT0/is (OR, 0.254; 95% CI, 0.111–0.583; P = .001) than HER2 IHC 2+/FISH-positive tumors. A significantly better pCR rate was also found in patients with T1 tumors and patients with dual HER2 blockade. The pCR rate was highly correlated with the HER2 IHC score in neoadjuvant anti-HER2 treatment. The addition of pertuzumab to a neoadjuvant trastuzumab-based regimen improved pCR rates, but there was no significant difference in pCR rates in the IHC 2+/FISH-positive group. This suggests that HER2 IHC scores can predict the effectiveness of treatment.